Changes in blood values in elite cyclist - Mørkeberg, J. S.; Belhage, B.; Damsgaard, R. (International Journal of Sports Medicine, 2009)
In 2006, a couple of professional cycling teams initiated their own testing programs. The objective of this study is to describe fluctuations in commonly measured blood parameters among top-level riders. From December 12th 2006 to November 30th 2007, a total of 374 blood samples and 287 urine samples were obtained from 28 elite, male cyclists. Blood was analyzed for hematocrit (Hct), hemoglobin concentration ([Hb]) and % reticulocytes. Seventy-six percent of all samples were collected out-of-competition (OOC). From December 2006 to September 2007, the average Hct and [Hb] decreased by 4.3 percent point and 1.3 g/dL, respectively. After the end of the competitive season, the values increased back to baseline levels. During the Tour de France, the [Hb] decreased by 11.5 %, with individual decreases ranging from 7.0 to 20.6 %. Hct and [Hb] values were lower in-competition (40.9 % and 14.1 g/dL) compared to OOC (43.2 % and 15.0 g/dL) and pre-competition (43.5 % and 14.9 g/dL). Our results suggest that when interpreting blood sample results in an anti-doping context, the sample timing (OOC, pre- or in-competition) and time of year should be kept in mind.